Pendampingan Guru SMPN 8 Kota Malang dalam Mengembangkan Perilaku Etis Siswa Berbasis Model Pembelajaran OIDDE - Husamah, Husamah; Hudha, Atok Miftachul; Pantiwati, Yuni (International Journal of Community Service Learning, 2018)
Based on the priority problem, we need an effective and appropriate solution to develop the students’ ethical behaviour of state junior high school 8 of Malang (SJHS/SMPN 8). This article aims to describe the implementation teacher mentoring activities in developing students' ethical behavior based on OIDDE learning model. The subject in this devotion were teachers, which consists of master teachers amounted to 10 people and other teachers amounted to 46 people. The activity was held for 8 months. In addressing the problems faced by partner schools, work procedures and methods of implementation of community development program that have been discussed and agreed with both partner schools, FGDs, workshops, direct practice, dissemination, and evaluation. The programs has been conducted, with activities in the form of: equation of perception, OIDDE learning workshop (speech by headmaster, exposure of executing chairman, essentials concepts (active learning development, character, authentic assessment), OIDDE model and examples, discussions, mentoring of learning tools, open class, and evaluation.